Fundamentals of femtosecond optics - Kozlov, S. A. (Sergei Arkadevich), 1956- (Woodhead Publishing series in electronic and optical materials ;, 2013)
Femtosecond optics involves the study of ultra-short pulses of light. Understanding the behaviour of these light pulses makes it possible to develop ultra-fast lasers with a wide range of applications in such areas as medical imaging, chemical analysis and micro-machining. Written by two leading experts in the field, this book reviews the theory of the interaction of femtosecond light pulses with matter, femtosecond lasers and laser systems, and the principles of femtosecond coherent spectroscopy of impurity amorphous media. reviews the theory of the interaction of femtosecond light pulses with matterDiscusses femtosecond lasers and laser systemsConsiders the principles of femtosecond coherent spectroscopy of impurity amorphous media.